2016
DOI: 10.1098/rspb.2016.1646
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structure and functioning of polar pelagic ecosystems to predict the impacts of change

Abstract: The determinants of the structure, functioning and resilience of pelagic ecosystems across most of the polar regions are not well known. Improved understanding is essential for assessing the value of biodiversity and predicting the effects of change (including in biodiversity) on these ecosystems and the services they maintain. Here we focus on the trophic interactions that underpin ecosystem structure, developing comparative analyses of how polar pelagic food webs vary in relation to the environment. We highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 62 publications
(219 reference statements)
0
105
0
Order By: Relevance
“…Their broad spatial distribution, long lifespans, and position at higher trophic levels mean that changes in their overall reproductive success, F I G U R E 2 Modeled distribution of fasting and non-fasting probabilities based on serum urea and creatinine levels in 1448 samples from subadult and adult polar bears captured in the Chukchi and Beaufort Seas 1983-2016 survival of age classes, and population size may be indicative of regional scale changes in the ecosystems in which they reside. Polar pelagic food webs consist of a small number of species where energy flows to higher trophic levels via fewer pathways than more complex systems (Murphy et al, 2016). This results in Arctic systems being sensitive to changes in abundance of keystone species, such as Arctic cod which link lower and higher trophic levels (Murphy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their broad spatial distribution, long lifespans, and position at higher trophic levels mean that changes in their overall reproductive success, F I G U R E 2 Modeled distribution of fasting and non-fasting probabilities based on serum urea and creatinine levels in 1448 samples from subadult and adult polar bears captured in the Chukchi and Beaufort Seas 1983-2016 survival of age classes, and population size may be indicative of regional scale changes in the ecosystems in which they reside. Polar pelagic food webs consist of a small number of species where energy flows to higher trophic levels via fewer pathways than more complex systems (Murphy et al, 2016). This results in Arctic systems being sensitive to changes in abundance of keystone species, such as Arctic cod which link lower and higher trophic levels (Murphy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Polar pelagic food webs consist of a small number of species where energy flows to higher trophic levels via fewer pathways than more complex systems (Murphy et al, 2016). This results in Arctic systems being sensitive to changes in abundance of keystone species, such as Arctic cod which link lower and higher trophic levels (Murphy et al, 2016). Spring fasting of the three polar bear subpopulations in this study varied temporally and spatially consistent with observed variation in measures of primary productivity and the health of prey and other species within their Arctic food web.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copepods and mesopelagic fish, particularly myctophids, are important primary and secondary consumers of the phytoplankton in these waters and form an alternative food web for squid, predatory mesopelagic fish, and penguins (Kozlov, 1995;Cherel et al, 2010;Murphy et al, 2016). Measured rates of microzooplankton grazing (Jones et al, 1998;Griffiths et al, 1999;Safi et al, 2007;Pearce et al, 2011), together with high grazer biomass (KopczyƄska et al, 2001) suggest that grazers consume much of the primary productivity in this region.…”
Section: Sub-antarctic Zonementioning
confidence: 99%
“…Thus, declines in ice algal abundance will likely have a significant negative effect on critical links in the SO food web, especially krill, and promote different and less energy efficient trophic pathways such as consumption of phytoplankton by salps or via copepods to myctophids. Such changes would reduce the capacity of the SO to support the current abundance of iconic, krill-dependent Antarctic wildlife (Murphy et al, 2007(Murphy et al, , 2016.…”
Section: Seasonal Sea Ice Zonementioning
confidence: 99%